2021
DOI: 10.5271/sjweh.3952
|View full text |Cite
|
Sign up to set email alerts
|

The associations of working hour characteristics with short sickness absence among part- and full-time retail workers

Abstract: Objective: This study aimed to determine the associations of working hour characteristics with short (1–3 days) sickness absence (SA) among retail workers. Methods: As part of “RetailHours-project”, 4046 employees of 338 Finnish retail stores were included. Registry-based data on working hour characteristics and short SA were utilized. A case-crossover design was used and the odds ratios (OR) were controlled for the clustering effect and working hour characteristics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…For instance, one study found that quick returns (< 11 h of rest between shifts) were associated with a higher risk of sickness absence, while night work was not [ 24 ]. Another study reported that working mainly night shifts was associated with short-term sickness absence among full-time retail workers [ 25 ]. One study indicated that two-shift rotation (days and evenings), three-shift rotation (days, evenings, and nights), and fixed night work were related to elevated short-term sickness absence, but findings were inconclusive for long-term sickness absence [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, one study found that quick returns (< 11 h of rest between shifts) were associated with a higher risk of sickness absence, while night work was not [ 24 ]. Another study reported that working mainly night shifts was associated with short-term sickness absence among full-time retail workers [ 25 ]. One study indicated that two-shift rotation (days and evenings), three-shift rotation (days, evenings, and nights), and fixed night work were related to elevated short-term sickness absence, but findings were inconclusive for long-term sickness absence [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many of the latter factors can also be considered as confounding variables. Some recent studies have adjusted for confounders, e.g., weekly work hours and length of shift [ 21 , 25 ], but the previous systematic review noted that many studies did not adjust for such variables [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the results of these studies are inconsistent. Some studies found higher rates of sickness absence among night shift workers ( 11 16 , 18 ) compared to workers on day shift, whereas other studies observed no relationship ( 12 , 17 , 19 ).…”
mentioning
confidence: 97%
“…Both shiftwork with and without night shifts have been linked to increased sickness absence, 7,8,10–14 although some studies also indicate that the relationship is dependent on the population and shift schedule 9,15,16 . In the present article, we therefore focus on two typical shift schedules: two-shift rotations, with day and evening shifts, and three-shift rotations, with day, evening, and night shifts.…”
mentioning
confidence: 99%
“…Both shiftwork with and without night shifts have been linked to increased sickness absence, 7,8,[10][11][12][13][14] although some studies also indicate that the relationship is dependent on the population and shift schedule. 9,15,16 In the present article, we therefore focus on two typical shift schedules: two-shift rotations, with day and evening shifts, and three-shift rotations, with day, evening, and night shifts. We investigate whether (1) a positive work environment can moderate the adverse consequences of shiftwork and (2) whether a poorer work environment can explain the high risk of absence identified among shiftworkers.…”
mentioning
confidence: 99%